Identification of Superior Soybean Cultivars through the Indication of Specific Adaptabilities within Duo-Environments for Year-Round Soybean Production in Northeast Thailand - Chompoonut Sritongtae; Tidarat Monkham; Jirawat Sanitchon; Sanit Lodthong; Sittipong Srisawangwong; Sompong Chankaew (Agronomy, 2021)
The soybean (Glycine max (L.) Merrill) is one of the world’s most important sources of food, feed, and fuel due to its high protein value and oil content. However, there exists a lack of soybean genotypes suitable for growth in diverse conditions as soybean breeders have developed their own varieties for specific purposes within their own unique environments. This, therefore, creates the need for soybean genotypes for different environments. The objectives of the experiment described herein were to determine the genotype magnitude through the environment interaction (GxE) of new soybean breeding lines, thereby identifying widely and/or specifically adapted genotypes under ten of Northeast Thailand’s typical environmental conditions from 2017 to 2019. Analyses of the environment (E) and GxE captured a large portion of the total sum of squares of grain yield and related traits, which demonstrated the influence of the two factors in evaluating soybean genotypes, thereby identifying the need for response analysis to identify superior genotypes in each environment. Based on the grain yields of three environments, four genotype groups were clustered. Within the high grain yield environment (EG1), we identified five genotypes with higher yield performance (35*sj-32 (3356 kg/ha), 38D*a-16 (3138 kg/ha), 42*Ly-50-2 (3122 kg/ha), 35*Lh-7 (3116 kg/ha), and 223*Lh-85 (3073 kg/ha)) of KK (3132 kg/ha), the recommended soybean variety for Northeast Thailand, than that of the CM60 (2606 kg/ha). These five top-yielding genotypes, however, produced unstable grain yields through varied environments as they were each narrowly adapted to a specific environment. Moreover, those genotypes may be grown within a rotational cropping system in a duo-environment (wet and dry season) of soybean production in Thailand’s northeast region.